Evaluation of three consumers' contribution to the current and voltage distortions at the point of common coupling - Shklyarskiy, Yaroslav; Dobush, Iuliia; Sutikno, Tole; Hatta Jopri, Mohd (Bulletin of Electrical Engineering and Informatics, 2023)
The article presents the method to evaluate share responsibility for the generation of harmonic currents between utility and consumer that are connected to the same point of common coupling (PCC). For these purposes, an indicator that evaluates the consumer's contribution to the distortion of current and voltage at the PCC is proposed, based on the previously carried out mathematical modeling of the power supply system (PSS) with two consumers. An evaluation of the distortion caused by three different non-linear loads on the consumers’ side is carried out in this study. The approbation of the proposed method was carried out on a laboratory bench, where various operation modes of linear and nonlinear loads were studied. Thus, the results proved that the proposed method could quantify the contribution of voltage and current distortion caused by three and more non-linear loads at the PCC of the consumer’s side. Besides, this proposed method can also be used to draw up recommendations for the mitigation of the harmonic currents compensation.